The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1071/fp18177
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in whole-plant transpiration efficiency in sorghum only partly aligns with variation in stomatal conductance

Abstract: Water scarcity can limit sorghum (Sorghum bicolor (L.) Moench) production in dryland agriculture, but increased whole-plant transpiration efficiency (TEwp, biomass production per unit of water transpired) can enhance grain yield in such conditions. The objectives of this study were to quantify variation in TEwp for 27 sorghum genotypes and explore the linkages of this variation to responses of the underpinning leaf-level processes to environmental conditions. Individual plants were grown in large lysimeters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…This points to a tradeoff between leaves with more numerous, smaller stomata which show high steady-state g s but rapid g s responses to PPFD, and leaves with fewer, larger stomata which show low steady-state g s but slow g s responses to PPFD. The finding that steady-state iWUE 2000 was mainly associated with g s 2000 rather than A 2000 is consistent with prior observations in sorghum (Geetika et al, 2019) and other C 4 grasses (Leakey et al, 2019), but the tradeoff with non-steadystate g s identified here (Figure 6) is not widely recognized.…”
Section: Decreases In Ppfd Substantiallysupporting
confidence: 90%
“…This points to a tradeoff between leaves with more numerous, smaller stomata which show high steady-state g s but rapid g s responses to PPFD, and leaves with fewer, larger stomata which show low steady-state g s but slow g s responses to PPFD. The finding that steady-state iWUE 2000 was mainly associated with g s 2000 rather than A 2000 is consistent with prior observations in sorghum (Geetika et al, 2019) and other C 4 grasses (Leakey et al, 2019), but the tradeoff with non-steadystate g s identified here (Figure 6) is not widely recognized.…”
Section: Decreases In Ppfd Substantiallysupporting
confidence: 90%
“…a limited maximum transpiration rate (TR) value in the high VPD hours of the day) described in a crop model [4] is also partially featured. Only few measurements have been done under natural conditions [12][13][14][15][16], with both temperature and relative humidity changing simultaneously over the course of the day. Those studies measured the expression of genotypic differences in the transpiration response to VPD only from the maximum transpiration values under high VPD conditions, and also had low throughput.…”
Section: Introductionmentioning
confidence: 99%
“…This trait provides insight into the genetics of TE, especially from the perspective of plant hydraulics, probably with close involvement of aquaporins (Vadez et al, 2014). However, recent studies (Geetika et al, 2019) have shown that while genetic variation in TE aligned with differences in stomatal conductance under high demand conditions, some of the remaining residual variation reflected differences in photosynthetic capacity. Further, Shekoofa, Sinclair, Messina, and Cooper (2015) demonstrated that the expression of the limited transpiration trait could be jeopardized under high temperatures.…”
Section: Crop Sciencementioning
confidence: 99%